Experiences of the changing illicit drug supply among racial and ethnic minoritized people in three US states: a qualitative study - Brendan Saloner; Olivia K. Sugarman; Lauren Byrne; Samantha Harris; Molly C. Reid; Hridika Shah; Eric Hulsey; Adrienne Hurst; Lindsey Kerins; Dionna King; Susan Sherman; Emily Kaner; et al. (Harm Reduction Journal)
Abstract Background Amidst a national surge in overdose deaths among racial and ethnic minoritized people and people who use stimulants (cocaine or methamphetamines), our objective was to understand how these groups are adapting to a rapidly changing illicit drug supply. Methods We conducted semi-structured interviews with 64 people who use drugs and who self-identified as Black, Hispanic, Multiracial, or other Non-White race in three states (Michigan, New Jersey, and Wisconsin). Transcribed interviews were coded thematically. Results Most respondents used stimulants alone or in combination with opioids. Respondents perceived that the drug supply had become more unpredictable and dangerous but differed in their personal perception of risk and their adaptations. For example, respondents had very mixed perceptions of their own risk of being harmed by fentanyl, and differing opinions about whether fentanyl test strips would be useful. Xylazine, a novel adulterant in the opioid drug supply that has received public health and media attention, was not well known within the sample. Conclusion Our study highlights the challenges experienced by minoritized people who use drugs in responding to a changing drug supply, underscoring the limits of public health approaches focused solely on individual behavioral change.